CTRP5-Overexpression Attenuated Ischemia-Reperfusion Associated Heart Injuries and Improved Infarction Induced Heart Failure - Peng, Meng; Liu, Yuan; Zhang, Xiang-qin; Xu, Ya-wei; Zhao, Yin-tao; Yang, Hai-bo (Frontiers in Pharmacology, 2020)
Aims: C1q/tumor necrosis factor (TNF)-related protein 5 (CTRP5) belongs to the C1q/TNF-α related protein family and regulates glucose, lipid metabolism, and inflammation production. However, the roles of CTRP5 in ischemia/reperfusion (I/R) associated with cardiac injuries and heart failure (HF) needs to be elaborated. This study aimed to investigate the roles of CTRP5 in I/R associated cardiac injuries and heart failure. Materials and Methods: Adeno-associated virus serum type 9 （AAV9）vectors were established for CTRP5 overexpression in a mouse heart (AAV9-CTRP5 mouse). AAV9-CTRP5, AMPKα2 global knock out （AMPKα2−/−）and AAV9-CTRP5+ AMPKα2−/− mice were used to establish cardiac I/R or infarction associated HF models to investigate the roles and mechanisms of CTRP5 in vivo. Isolated neonatal rat cardiomyocytes (NRCMS) transfected with or without CTRP5 adenovirus were used to establish a hypoxia/reoxygenation (H/O) model to study the roles and mechanisms of CTRP5 in vitro. Key Findings: CTRP5 was up-regulated after MI but was quickly down-regulated. CTRP5 overexpression significantly decreased I/R induced IA/AAR and cardiomyocyte apoptosis, and attenuated infarction area, and improved cardiac functions. Mechanistically, CTRP5 overexpression markedly increased AMPKα2 and ACC phosphorylation and PGC1-α expression but inhibited mTORC1 phosphorylation. In in vitro experiments, CTRP5 overexpression could also enhance AMPKα2 and ACC phosphorylation and protect against H/O induced cardiomyocytes apoptosis. Finally, we showed that CTPR5 overexpression could not protect against I/R associated cardiac injuries and HF in AMPKα2−/− mice. Significance: CTRP5 overexpression protected against I/R induced mouse cardiac injuries and attenuated myocardial infarction induced cardiac dysfunction by activating the AMPKαsignaling pathway.